2003
DOI: 10.1267/ahc.36.193
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Visualization of Intracellular Ca2+ in Living Heart Muscle Cells Viewed by Confocal Laser Scanning Microscopy.

Abstract: Ca 2+ ions play pivotal roles in the excitation and contraction-relaxation processes of heart muscle cells. The advent of digital-imaging techniques, especially confocal laser scanning microscopy, as well as Ca 2+-sensitive fluorescent dyes, has contributed substantially to the precise understanding of the spatiotemporal aspects of the intracellular Ca 2+ dynamics in cardiomyocytes. In this review article, we review the progress in the cytochemical and histochemical researches on the intracellular Ca 2+ concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 70 publications
(64 reference statements)
1
10
0
Order By: Relevance
“…By using our unique in situ rapid‐scanning confocal microscopy, we found that during consecutive heartbeats, individual myocytes exhibit spatiotemporally uniform Ca 2+ transients on excitation, while there is no remarkable [Ca 2+ ] i elevation during diastole (Fig. S1B) . In contrast, myocytes under [Ca 2+ ] i overload, caused by, e.g., membrane damage, exhibit spontaneous wave‐like elevations of local [Ca 2+ ] i that propagate within the individual myocytes, called Ca 2+ waves (Fig.…”
Section: Arrhthomogenesis Revealed By Functional Imaging Of Non‐electmentioning
confidence: 98%
See 1 more Smart Citation
“…By using our unique in situ rapid‐scanning confocal microscopy, we found that during consecutive heartbeats, individual myocytes exhibit spatiotemporally uniform Ca 2+ transients on excitation, while there is no remarkable [Ca 2+ ] i elevation during diastole (Fig. S1B) . In contrast, myocytes under [Ca 2+ ] i overload, caused by, e.g., membrane damage, exhibit spontaneous wave‐like elevations of local [Ca 2+ ] i that propagate within the individual myocytes, called Ca 2+ waves (Fig.…”
Section: Arrhthomogenesis Revealed By Functional Imaging Of Non‐electmentioning
confidence: 98%
“…6,15 In contrast, myocytes under [Ca 2þ ] i overload, caused by, e.g., membrane damage, exhibit spontaneous wave-like elevations of local [Ca 2þ ] i that propagate within the individual myocytes, called Ca 2þ waves ( Fig. S2A), 6,7,15 wellestablished Ca 2þ release events from the SR ( Fig. S2B & C).…”
Section: Roles Of Intracellular Ca 2þ Waves In Triggered Arrhythmiasmentioning
confidence: 99%
“…In particular, unknown is whether the [Ca 2+ ] i overload is the only culprit for the contracture. With the advent of live-cell imaging technology, especially in situ real-time confocal microscopy, both the [Ca 2+ ] i dynamics and structure of the individual myocytes can be simultaneously visualized in the working heart [ 14 , 18 , 30 ]. This imaging modality, if applied to the heart under the Ca 2+ -paradox injury, would enable us to address the mechanism(s) underlying development of myocyte contracture.…”
Section: Introductionmentioning
confidence: 99%
“…The entering Ca 2+ triggers release of Ca 2+ from the sarcoplasmic reticulum (SR) through a process known as Ca 2+ ‐induced Ca 2+ release (CICR), which allows a transient increase in the cytosolic [Ca 2+ ] i , that is, a Ca 2+ transient, leading to contraction via Ca 2+ binding to the contractile protein, troponin C. Subsequent membrane repolarization produces decline of [Ca 2+ ] i to the basal (i.e. diastolic) levels by means of re‐uptake of Ca 2+ into the SR by Ca 2+ pump (sarco(endo)plasmic reticulum calcium ATPase (SERCA)) or Ca 2+ extrusion by Ca 2+ pump and Na + /Ca 2+ exchange in the sarcoplasm 27 …”
Section: Arrhythmogenic Disturbance Of Intracellular Calcium Ion Dynamentioning
confidence: 99%
“…The lower image, agonal waves. Reproduced with permission from Takamatsu and Wier (1990) 8 and Tanaka and Takamatsu (2003) 27 . See also Supplementary Movie S1.…”
Section: Arrhythmogenic Disturbance Of Intracellular Calcium Ion Dynamentioning
confidence: 99%